Sindroma Marfan – Laporan Kasus - Manoppo, Rillya (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: Marfan's syndrome is a FBN1 gene mutation that encodes a connective tissue protein, fibrillin-1. Patients usually present with multiple defects including mayor ocular system abnormalities such as ectopic lens and minor criteria such as flat normal cornea, various axial lengths, ciliary hypoplasia, and myopia. We reported a case of a 6-year-old boy with vision complaint since one year ago. Ophthalmological examination revealed 6/60 right eye vision and 1/60 left eye vision. The pressure of the right eyeball was 15 mmHg and of the left eyeball was 13 mmHg. Eye vision could not be corrected with lenses. There were normal eyeball movements to all directions. Examination of the anterior segment showed no injection, clear cornea, and clear anterior chamber. There were superonasal subluxation of the right eye lens with zonular pull and superotemporal subluxation of the left eye lens with zonular pull. Examination of the posterior segment showed positive non-uniform fundus reflex, however, examination of the vitreous body, retina, and macula was difficult to evaluate. The patient was treated with lens extraction and was advised to come to the eye clinic every month for further evaluation of the eye ball pressure and ophthalmological examination as well as the possibility of further intervention treatment such as anterior lens implant in the anterior chamber.Keywords: Marfan syndrome, ectopic lensAbstrak: Sindrom Marfan adalah mutasi gen FBN1 yang mengkode protein jaringan ikat yang disebut fibrilin-1. Pasien biasanya datang dengan cacat multipel termasuk kelainan pada sistem okular yang meliputi kriteria mayor berupa ektopia lentis dan kriteria minor berupa kornea normal datar, peningkatan panjang aksial, hipoplasia silia, dan miopia. Kami melaporkan kasus seorang anak laki-laki berusia 6 tahun dengan keluhan penglihatan kedua mata kabur sejak 1 tahun lalu. Pada pemeriksaan oftalmologik didapatkan visus mata kanan 6/60, visus mata kiri 1/60, tekanan bola mata kanan 15 mmHg, dan tekanan bolamata kiri 13 mmHg. Visus kedua mata tidak dapat dikoreksi dengan menggunakan lensa. Gerakan bola mata baik ke segala arah. Pemeriksaan segmen anterior menunjukkan tidak terdapat injeksi, kornea jernih, dan bilik mata depan jernih. Lensa mata kanan mengalami subluksasi ke arah superior nasal dengan tarikan zonula Zinii sedangkan lensa mata kiri mengalami subluksasi ke arah superior temporal dengan tarikan zonula Zinii. Pemeriksaan segmen posterior kedua mata didapatkan refleks fundus positif non-uniform, sedangkan pemeriksaan untuk badan vitreus, retina dan makula sulit dievaluasi. Tindakan yang dilakukan berupa ekstraksi lentis. Pasien diminta untuk kontrol berkala di poliklinik mata setiap bulan untuk menilai tekanan bola mata dan status oftalmologiknya serta kemungkinan intervensi lanjutan seperti pemasangan lensa anterior pada bilik mata depan.Kata kunci: sindrom Marfan, ektopia lentis